Recycling of Waste Glass as Partial Replacement to Fine Aggregate and Rice Husk Ash as Partial Replacement of Cement in Concrete Production - Shaikh, Shahid Ali; Ali Mangi, Sajjad; Buriro, Sajjad Hussain; Keerio, Manthar Ali; Soomro, Faheem Ahmed (Journal of Structural Monitoring and Built Environment, 2022)
The Recycled Waste Glass (RWG) is a most suitable substitute to the natural sand to be utilized in the concrete manufacturing industry and Rice Husk Ash (RHA) is an agricultural by-product having enormous characteristics to utilize as cementitious material in concrete. This study was carried out to understand the effects of RHA as partial replacement to cement and RWG as a partial replacement to natural fine aggregate with 10%, 20% and 30% levels of substitutions in the concrete mixes respectively. The effects were investigated on the workability and compressive strength characteristics of fresh and hardened concrete. A total of 4 mixtures were prepared for M15 grade concrete with 1:2:4 concrete proportions and water to cement ratio of 0.55. Out of them one was controlled mixture and three were with 10%, 20% and 30% equal substitution levels of combined RHA and RWG. The acquired results showed that the slump values were like that of conventional concrete at combined incorporation of RHA and RWG at 10% replacement, but a decline was noticed at 20% and 30% replacement. The decline was due to the more surface area of RHA which absorbs more water. The compressive strength at 10%RHA and 10% RWG combined replacement in concrete mix was increased by 9.7% as compared to controlled mix after 28 days curing. The results were similar at 20%RHA and 20%RWG incorporation as compared to controlled concrete mix. It is concluded that RHA and RGW can be utilized at 10% equal replacement in the concrete and the cost of construction can be reduced. This research work will be helpful in developing a comprehensive scientific data base on combined utilization of RHA and RWG in the concrete mixes and the upcoming scientists, scholars and students will be benefitted.